An experimental investigation of the effect of TV cooking show consumption on children's food choice behaviour. (26th March 2018) - Ngqangashe, Yandisa; De Backer, Charlotte J.S.; Hudders, Liselot; Hermans, Nina; Vandebosch, Heidi; Smits, Tim
Abstract: For several decades, television consumption has been crucial in the complex web of factors underlying the obesity epidemic. It has been suggested that if television cooking shows would endorse healthy eating styles, they may have positive effects on consumers' eating habits. This study empirically investigated the consequences of exposing children ( N = 85, aged 9–12 years) to an existing television cooking show episode endorsing the consumption of fruits and vegetables compared with exposure to a non‐food‐related science show. The measures included pre‐test and post‐test attitudes toward health/nutrition and fruits/vegetables, as well as state preferences for a list of healthy and unhealthy foods. At the end of the study, children were separately given the choice between a popular cookie and a piece of fruit as a reward; this was used as a behavioural measure. The results of a logistic regression on the behavioural choice measure showed that the mere exposure to one episode of the television cooking show significantly increased the odds that the children would choose a piece of fruit over a cookie. Repeated‐measures analyses showed that watching this single episode also decreased children's state appetite for unhealthy foods. State appetites for healthy foods and attitudes toward health/nutrition or fruits/vegetables did not change after watching the television cooking show episode. In sum, existing television cooking shows that endorse healthy eating positively influence children's food consumption in the short term and may have the potential to be used as platforms for nutrition education.